Predictive risk factors for the development of diseases with lymphoproliferative syndrome in children - R. F. Makhmutov (Scientific Сentre for Family Health and Human Reproduction Problems, 2021)
Background. Harmful environmental factors and negative social trends have an adverse effect on the adaptive resources of the child’s body, which in combination reduces the health index in the child population. An ambiguous epidemiological situation, an increase in morbidity rates in children, a variety of clinical manifestations of Epstein – Barr viral infection, recurrent respiratory diseases, adenovirus infection complicate their differential diagnosis in the early stages. In this regard, the assessment of risk factors and early prognosis of the development of primary form of Epstein – Barr viral infection (EBVI), recurrent respiratory diseases (RRD), adenovirus infection (ADVI) in children is an urgent task.The aim: to study the significance of risk factors influencing the development of diseases with lymphoproliferative syndrome in children.Materials and methods. Clinical and laboratory examination and analysis of case histories of 336 children and adolescents held with diseases with lymphoproliferative syndrome. Data from 30 apparently healthy children and adolescents of the same age were used as a comparison group. The Bayesian method with sequential Wald analysis was used to assess risk factors. ROC-analysis was used to check the adequacy of the forecasting models. The quality of the built models was evaluated by their sensitivity and specificity.Results. It has been established that predictors of diseases with lymphoproliferative syndrome in children are intrauterine fetal hypoxia, low or, on the contrary, high birth weight, neonatal jaundice, low Apgar score, as well as maternal factors (somatic pathology and SARS during pregnancy, gestosis, gestational anemias, young or mature age of the pregnant women). Additional predictors of the development of this pathology can be considered a decrease in the indicator of the cell-phagocytic potential to 337.1 ± 2.3 CU, a decrease in the immune-lymphocytic potential to 237.0 ± 8.2 CU, an increase in the load-erythrocyte coefficient to 0.67 ± 0.03 CU and a decrease in the leukocyte index of intoxication to 0.40 ± 0.05 CU.Conclusion. The combination of clinical and anamnestic factors with indicators of general reactive potential increases the integral general informative value of the prognostic model. The accounting by specialists of the general medical and preventive network of the identified predictors of the development of diseases with lymphoproliferative syndrome will contribute to the timely diagnosis of the primary form of Epstein – Barr viral infection, recurrent respiratory diseases and adenovirus infection in children.